Efficacy of N-acetylcysteine in preventing amphotericin B induced acute kidney injury - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Objectives: Previously, in an animal study we showed that N-acetylcysteine (NAC) could decrease deoxycholate amphotericin B (DAmB) induced renal tubular apoptosis. In this clinical study, we aimed to evaluate the efficacy of NAC in preventing acute kidney injury (AKI) in febrile neutropenic patients with invasive pulmonary aspergillosis treated with DAmB. Patients and Methods: Thirty-three patients were included in the study. 17 patients were randomly placed into the DAmB group and 16 were randomly placed into the DAmB plus NAC group. Results: The characteristics of patients, durations and cumulative doses of DAmB, concurrent nephrotoxic drugs and basal serum creatinine (SCr) levels of patients were similar. Occurrence of a 1.5 fold or greater increase in the concentration of basal SCr and serum electrolytes were observed prospectively. The overall AKI was found in 13 patients (76.4%) in DAmB group and 6 patients (37.5%) in combination group (P = 0.024). No significant difference was observed in hypokalemia incidence between the groups (87.5 % in combination vs. 94.1 % in DAmB only groups). Conclusion: This clinical pilot study showed that NAC may be a promising anti-oxidant agent to decrease DAmB-induced AKI in febrile neutropenic patients.
Keywords: Amphotericin B; Acute kindey injury; N-acetyl cysteine; Febrile neutropenia